Education in a warming world: Trends, opportunities and pitfalls for institutes of higher education - Kelly, Orla; Illingworth, Sam; Butera, Fabrizio; Dawson, Vaille; White, Peta; Blaise, Mindy; Martens, Pim; Schuitema, Geertje; Huynen, Maud; Bailey, Susan; Cowman, Sian (Frontiers in Sustainability, 2022)
Higher education institutes (HEI) face considerable challenges in navigating how to respond to the escalating and intertwined socio-ecological sustainability crises. Many dedicated individuals working in the sector are already driving meaningful action through rigorous research, teaching, knowledge sharing, and public engagement, while there is a growing consensus that sector-wide change is needed to ensure that aspirational declarations and positive individual actions translate into sustainable and transformative change (UNESCO 2022; ALLEA 2022). This article seeks to contribute to such efforts by illustrating a number of trends, examples, and reflections on how third-level educational institutes can act sustainably. Drawing on McCowan’s (2020) framework we highlight the potential of five strategies HEI could employ to support the creation of a more sustainable future namely, i) innovative approaches to climate change education; ii) research agendas for societal transformations; iii) providing climate change education for professional development; iv) supporting public intellectuals; and iv) investing in whole-systems approaches to greening the campus. The insights are the product of an interdisciplinary working group with members from across Europe, Australia, and the UK. These international examples provide insight and a sense of possibility for future application.